2012
DOI: 10.1177/1091142112438460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of State-Level Tax and Expenditure Limits (TELs) on Government Revenues and Aid to Local Governments

Abstract: This article investigates the impact of state-level tax and expenditure limits (TELs) on state government revenues and aid to local governments. Using an instrumental variable approach to control for endogeneity, the authors find that the general fund TELs (i.e., revenue and expenditure limits) have led to substantial increases in tax and nontax revenues. States with procedural limits (i.e., those with voter approval and/or legislative supermajority requirements votes) have significantly lower tax revenues. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Our null hypothesis is that our instruments are weak and subject to bias that we find unacceptably large. The F-statistic from the weak identification test is larger than the Stock and Yogo (2005) critical value (13.91) in each of five specifications, an indicator that our excluded instruments are correlated with the 16 Kioko and Martell (2012) found voter initiative provisions were not valid instruments in their study of the impact of state-level TELs. They argue initiative processes have been used to alter the direction of state and local government policies (Waters 2003), as such voter initiative provisions were an important explanatory variable that could be used to not only explain the presence of the endogenous variable, but also have an independent effect on taxing and spending levels.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Our null hypothesis is that our instruments are weak and subject to bias that we find unacceptably large. The F-statistic from the weak identification test is larger than the Stock and Yogo (2005) critical value (13.91) in each of five specifications, an indicator that our excluded instruments are correlated with the 16 Kioko and Martell (2012) found voter initiative provisions were not valid instruments in their study of the impact of state-level TELs. They argue initiative processes have been used to alter the direction of state and local government policies (Waters 2003), as such voter initiative provisions were an important explanatory variable that could be used to not only explain the presence of the endogenous variable, but also have an independent effect on taxing and spending levels.…”
Section: Resultsmentioning
confidence: 81%
“…Like Rueben (1997), Shadbegian (1999), Knight (2000), Wagner (2004), and Kioko and Martell (2012), I apply an Instrumental Variable (IV) approach to address endogeneity of the policy variables of interest. I specify the IV model as follows:…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to state highway spending, Mullins and Joyce (1996, p. 91) found that ''state limits are associated with an initial reduction in the relative level of expenditures made by the state but expenditures tend to regain lost ground over time.'' Following Kioko and Martell (2012), I included a binary indicator of whether a state had a tax and expenditure limit and another dummy variable for voter approval or legislative super majority vote for new or higher taxes. Four widely used BBR-related binary variables specified in I indicate (1) whether a state's governor must submit a balanced budget, (2) whether the legislature must pass a balanced budget, (3) whether the governor must sign a balanced budget, and (4) whether current year-end deficit can be carried over into the next fiscal year (Hou and Smith 2006).…”
Section: Empirical Model and Strategymentioning
confidence: 99%
“…That's a very different issue than how the first generation TELs actually impacted state fiscal outcomes. Our perspective also sets aside the procedural rules issue (Kioko and Martell, 2012); that is, how TEL effectiveness varies with rules for changing a TEL's constraints on revenue or exclusions.…”
Section: Introductionmentioning
confidence: 99%